1998
DOI: 10.2516/ogst:1998006
|View full text |Cite
|
Sign up to set email alerts
|

Adsorption Isotherms of Phenol and 4-Chlorophenol on Petroleum Asphaltenes

Abstract: Les isothermes d'adsorption du phŽnol et du 4-chlorophŽnol en solution dans l'eau sur des asphalt•nes floculŽs en masse et sur des asphalt•nes dŽposŽs sur de la silice ont ŽtŽ dŽterminŽs par analyse chromatographique frontale ˆ 293, 298, 303 et 308 K. L'adsorption sur des asphalt•nes floculŽs en masse Žtait la plus importante avec des isothermes correspondant ˆ un mŽcanisme de Freundlich. La quantitŽ ŽlevŽe de phŽnols adsorbŽs sugg•re une migration possible des molŽcules du phŽnol ˆ travers la structure peu co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
11
0

Year Published

2001
2001
2020
2020

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(13 citation statements)
references
References 4 publications
2
11
0
Order By: Relevance
“…Similar isotherms have been reported for the adsorption of monohydric phenols and many monosulfonated dyes onto polar substrates from a polar solvent like water 28. Jaoui, M. et al, 1998 also reported similar isotherms for the adsorption of phenol and 4‐chlorophenol onto petroleum asphaltenes 31…”
Section: Resultssupporting
confidence: 68%
See 1 more Smart Citation
“…Similar isotherms have been reported for the adsorption of monohydric phenols and many monosulfonated dyes onto polar substrates from a polar solvent like water 28. Jaoui, M. et al, 1998 also reported similar isotherms for the adsorption of phenol and 4‐chlorophenol onto petroleum asphaltenes 31…”
Section: Resultssupporting
confidence: 68%
“…For the initial part of the S ‐curves, the more solute there is already adsorbed, the easier it is for additional solute to adsorb. This implies a side‐by‐side association between adsorbed molecules helping to hold them to the surface through ‘cooperative adsorption’ 28–31. Similar isotherms have been reported for the adsorption of monohydric phenols and many monosulfonated dyes onto polar substrates from a polar solvent like water 28.…”
Section: Resultssupporting
confidence: 66%
“…Dodecylbenzenesulfonic acid (DBSA) has been found to effectively stabilize asphaltenes. It is because DBSA can be adsorbed to the asphaltene surface via acid–base interactions and the alkyl chains of the absorbed DBSA form a protective layer that provides steric stabilization for asphaltenes. , Furthermore, studies revealed that the efficacy of an amphiphilic additive depends on its ability to be adsorbed onto the asphaltene surface. Although the stabilizers for asphaltenes have been investigated for a long time, the previous researches mainly focused on the small amphiphilic molecules. , A few recent studies concentrated on the polymeric stabilizers for asphaltenes. Chang and Fogler found that dodecylphenolic resin and poly­(octadecene- co -maleic anhydride) with multiple polar groups were able to stabilize asphaltenes by the associations with asphaltenes.…”
Section: Introductionmentioning
confidence: 99%
“…Dissolution of asphaltene particles using dispersants is a two-step process (Permsukarome et al, 1997;Jaoui et al, 1998;Leon et al, 1999): (1) the dispersants are adsorbed on the surface of the asphaltene particles and (2) the interactions between adsorbed dispersant and asphaltene becomes dominant, which results in formations of asphaltene-dispersant complexes. The reactions between the dispersants and asphaltene particles are as follows:…”
Section: Mechanism Of Asphaltene Dissolution Using Asphaltene Dispersmentioning
confidence: 99%
“…These kinds of isotherms are related to a two-step adsorption mechanism mentioned earlier. In a separate study, Jaoui et al (1998) measured the asphaltene isotherms for different combinations of dispersantscrude oils. Based on the results, they also concluded that the asphaltene-dispersant interaction is a two-step process.…”
Section: Mechanism Of Asphaltene Dissolution Using Asphaltene Dispersmentioning
confidence: 99%